The Effect of Tenure and Reputation of Public Accounting Firms toward Audit Quality: Case Mandatory Rotation of Auditors in Indonesia - Efraim Ferdinan Giri (The Indonesian Journal of Accounting Research, 2013)
The finance minister of Indonesia has issued a series of regulations governing the compulsory rotation of public accounting firms and auditors since 2003. It culminates with the issuance of finance minister regulation No.17/Menkeu.01/2008, which limits the provision of auditing services to three years for auditors and six years for public accounting firms. This study is motivated by the issuance of the finance minister rules and the equivocal of research findings. This study examines whether auditor tenure reduces audit quality in Indonesia. Further, this research investigates the effect of firm's reputation on audit quality. Using 455 firm-years in manufacturing industries listed in the Indonesian Stock Exchange, this research shows that audit tenure negatively affects audit quality. However, we find that reputation does not affect audit quality.